2019
DOI: 10.1016/j.ygyno.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity in gynecologic oncology

Abstract: Objectives-Financial toxicity is increasingly recognized as an adverse outcome of cancer treatment. Our objective was to measure financial toxicity among gynecologic oncology patients and its association with demographic and disease-related characteristics; self-reported overall health; and cost-coping strategies. Methods-Follow-up patients at a gynecologic oncology practice completed a survey including the Comprehensive Score for Financial Toxicity (COST) tool and a self-reported overall health assessment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 18 publications
3
66
3
2
Order By: Relevance
“…To the best of our knowledge, the current study is the first to report the responsiveness of COST. The Chinese version showed significant differences between the values at baseline and after 6 months of therapy, indicating that the instrument is The median COST value was 18 in this study, which was lower than that of the J o u r n a l P r e -p r o o f previous studies with 23 to 29 in US patients 14,[23][24][25] and 22 in Japanese cancer patients. 26 Our study showed that younger age, lower household income and URBMI were associated with worse FT.…”
Section: Discussioncontrasting
confidence: 80%
“…To the best of our knowledge, the current study is the first to report the responsiveness of COST. The Chinese version showed significant differences between the values at baseline and after 6 months of therapy, indicating that the instrument is The median COST value was 18 in this study, which was lower than that of the J o u r n a l P r e -p r o o f previous studies with 23 to 29 in US patients 14,[23][24][25] and 22 in Japanese cancer patients. 26 Our study showed that younger age, lower household income and URBMI were associated with worse FT.…”
Section: Discussioncontrasting
confidence: 80%
“…Another study conducted among patients with gynaecological cancer also reported that women with financial hardship are seven times more likely to avoid or delay their cancer care. 25 Providing free diagnostic and treatment services to all women with cervical cancer needs to be incorporated into the government's strategy on cervical cancer care. This will be in line with the WHO's global efforts to ensure universal health coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to quantify the experience of cancer patients related to financial difficulties during cancer treatment, the North American group Functional Assessment of Chronic Illness Therapy (FACIT) developed and validated [ 6 ] the COST questionnaire, with 11 items plus one considered a summary of all the questions. The answers are on a five-point Likert scale that measures the financial toxicity of the cancer patient, considered by some authors [ 11 , 12 ] as a side effect of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%